Preliminary evaluation of "Clearview Chlamydia" for the rapid detection of chlamydial antigen in cervical secretions. Issue 2 (April 1991) - Young, H; Moyes, A; Lough, H; Smith, I W; McKenna, J G; Thompson, C
Abstract : Clearview Chlamydia (Unipath) is a rapid monoclonal antibody based latex immunodiffusion test for detecting chlamydial antigen in endocervical specimens. The assay does not require specialised equipment or extensive training and takes less than 30 minutes from sample to results. The clinical performance of Clearview Chlamydia was evaluated with 478 paired endocervical swabs from patients attending a genitourinary medicine clinic. In the first part of the study, 221 non-randomised specimens were tested by cell culture (1st swab) and Clearview (2nd swab) whereas in the second part of the study 257 randomised swabs were examined by Clearview, cell culture and immunofluorescence. The overall prevalence of chlamydial infection was 8.8% and the sensitivity, specificity, positive and negative predictive values for Clearview were 85.7%, 99.1%, 90% and 98.6%. The test requires further evaluation to establish its role in the management and control of chlamydial infection.